Determinants of Peripapillary and Macular Vessel Densities Measured by Optical Coherence Tomography Angiography in Normal Eyes. Issue 5 (May 2017) - Rao, Harsha L.; Pradhan, Zia S.; Weinreb, Robert N.; Reddy, Hemanth B.; Riyazuddin, Mohammed; Sachdeva, Sonia; Puttaiah, Narendra K.; Jayadev, Chaitra; Webers, Carroll A.B.
Abstract : Purpose: The aim of this study was to evaluate the effect of subject-related (age, sex, and systemic hypertension and diabetes), eye-related (refractive error, optic disc size), and technology-related (signal strength index, SSI of the scans) determinants on the peripapillary and macular vessel densities measured with optical coherence tomography angiography (OCTA) in normal eyes. Methods: In a cross-sectional study, 181 normal eyes of 107 subjects (45 men, 62 women, median age: 50 y, range: 18 to 77 y) underwent OCTA imaging. Linear mixed models were used to analyze the effect of the determinants on the peripapillary and macular vessel densities measured with OCTA. Results: It was found that age and optic disc size did not affect the vessel densities of any of the regions ( P >0.05 for all associations). En face optic disc (coefficient: 1.67, P <0.001) and most of the peripapillary vessel densities were higher in female individuals. En face disc (coefficient=−1.88, P =0.02) and most of the peripapillary vessel densities were lower, whereas the parafoveal vessel density was higher (coefficient=2.32, P =0.01), in subjects with hypertension. Most of the vessel densities were lower in subjects with diabetes. SSI showed a statistically significant association with the vessel densities of all regions (coefficients: 0.14 to 0.27 for peripapillary and 0.20 to 0.27 for macular sectors). Conclusions: Most of the peripapillary vessel densities were higher in female subjects. Hypertension and diabetes also affected the vessel densities. Vessel densities in all the regions were significantly higher in scans with higher SSI. These results should be considered when interpreting the vessel densities in retinal diseases and glaucoma.